2017
DOI: 10.1111/jpet.12263
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, impatience, and dynamic private provision of a discrete public good

Abstract: We analyze dynamic private provision of a discrete public good by heterogeneous agents, who differ in terms of their levels of impatience, in a differential game framework. In contrast to the strategic complementarity result for homogeneous individuals, we show that an asymmetric completion Markov perfect equilibrium exists, where the individual contributions and the strategic behaviors depend crucially on an impatience differential: the difference in rates of time preference across groups of individuals. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…If the objective functions of the agents are asymmetric, the analysis of differential games becomes substantially difficult. List and Mason (), Woo (), Long and Sorger (), and Bhattacharya, Tokovenko, and Sardana () are exceptional studies examining such an asymmetric case. In our study, however, the objective functions of agents are significantly different compared with previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…If the objective functions of the agents are asymmetric, the analysis of differential games becomes substantially difficult. List and Mason (), Woo (), Long and Sorger (), and Bhattacharya, Tokovenko, and Sardana () are exceptional studies examining such an asymmetric case. In our study, however, the objective functions of agents are significantly different compared with previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In voting environments in which the set of alternatives is a metric space and each agent's preference is represented by a continuous utility function, they showed that, if the social choice function satisfies strategy-proofness and its range contains at least three alternatives, 1 See Clarke (1971), Moulin (1994), and Serizawa (1996Serizawa ( , 1999 for nonexcludable public good economies. In addition, see Caplan (2016), Maldonado and Rodrigues-Neto (2016), and Bhattacharya, Tokovenko, and Sardana (2017) for recent theoretical studies on nonexcludable public good economies.…”
Section: Introductionmentioning
confidence: 99%
“…See Clarke (), Moulin (), and Serizawa (, ) for nonexcludable public good economies. In addition, see Caplan (), Maldonado and Rodrigues‐Neto (), and Bhattacharya, Tokovenko, and Sardana () for recent theoretical studies on nonexcludable public good economies. …”
mentioning
confidence: 99%
“…The pioneering works of Warr (), Bergstrom et al (), and Andreoni (), have motivated much important research on the private provision of public goods which have been an important area for Journal of Public Economic Theory (cf., Barbarari & Malueg, ; Bhattacharya, Oleksiy, & Sardana, ; Caplan, , among many others). One such paper in this issue is Barbieri and Malueg (), who study private provision in a public goods game with incomplete information in which the level of the public good equals the least contribution made by a player.…”
mentioning
confidence: 99%